2015
DOI: 10.1063/1.4936786
|View full text |Cite
|
Sign up to set email alerts
|

On the dynamics of a subnanosecond breakdown in nitrogen below atmospheric pressures

Abstract: The dynamics of a breakdown in a gas-filled diode with a highly inhomogeneous electric field was studied in experiments at a time resolution of $100 ps and in numerical simulation by the 2D axisymmetric particle-in-cell (PIC) code XOOPIC. The diode was filled with nitrogen at pressures of up to 100 Torr. The dynamics of the electric field distribution in the diode during the breakdown was analyzed, and the factors that limit the pulse duration of the runaway electron beam current at different pressures were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 20 publications
0
7
0
3
Order By: Relevance
“…From all the statements about the RAEs at the breakdown in SF 6 , air and nitrogen mentioned above, it is easy to understand that there is no consensus of opinions regarding the characteristics of RAEs in air and heavy gases and their generation mechanism among scientific teams [1–27]. Therefore, it is necessary to carry out new research to eliminate misunderstandings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From all the statements about the RAEs at the breakdown in SF 6 , air and nitrogen mentioned above, it is easy to understand that there is no consensus of opinions regarding the characteristics of RAEs in air and heavy gases and their generation mechanism among scientific teams [1–27]. Therefore, it is necessary to carry out new research to eliminate misunderstandings.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the amplitude of a runway electron beam current realised in SF 6 with a tubular cathode of 6 mm in diameter at the voltage rise time of ∼2 ns increased considerably as the gap width was decreased from 12 to 8 mm [32]. Reasoning that the beam amplitude is determined by the voltage across the gap, all other things being equal, at the instant of generation of runaway electrons [1–27], it can be assumed that a decrease in the electrode spacing increased the gap voltage [32]. The assumption is indirectly supported by research data on a runaway electron beam produced in nitrogen with the gap of 12 mm and tubular cathode with the diameter of 6 mm at the voltage rise time of 0.3 ns [33], showing a considerable increase in the voltage across the gap and the beam current amplitude with a decrease in the pressure.…”
Section: Introductionmentioning
confidence: 99%
“…To study the influence of cathode emission on the runaway electron beam parameters, we considered the pulses, in which the rise time of incident voltage wave and the voltage amplitude were identical. It has been shown in [8], that the duration of beam current in nitrogen at 30 Torr pressure is limited by the foil, which separates the diode and the beam-measuring unit precluding the passage of electrons with the energies below 40 keV. That is, the beam current amplitude at such pressures depends only on the time of the onset of emission processes at the cathode.…”
Section: Introductionmentioning
confidence: 99%
“…The emission was described using a model [8] covering both the field emission (the early breakdown stage) and the transition to explosive emission (the unlimited emission ability of cathode). The field emission was described by a modified Fowler-Nordheim formula for a cathode covered with microprotrusions having different amplification factors The above-mentioned formula includes an average amplification factor < characterizing the state of its emission surface: The average current density estimated by formula (1) was multiplied by the total surface area…”
Section: Numerical Simulationmentioning
confidence: 99%
See 1 more Smart Citation